Peran KPID Jawa Barat dalam Pelaksanaan Sosialisasi Literasi Media Menggunakan Media Sosial (Faculty of Communications Science, Dr. Soetomo University, 2018)
West Java is the province with the largest number of local television. The existence of broadcasting institutions should be submitted to the public by KPID West Java to fulfill the public's right. The media literacy socialization using Twitter to West Java people is done to to strengthen the existence of broadcasting institutions. The author uses a case study research method. The author has made a direct observation and recording systematically on the socialization of media literacy, the process of field observation during socialization, the programs undertaken to encourage media literacy movement during the research conducted the whole program which distributed to the community in KPID West Java Twitter. The function of Twitter's is to realize the media literacy program by aligning communication, transparency, KPID West Java activities information that have the ultimate goal to strengthen the public relations of viewers / listeners with KPID West Java. Keywords: KPID West Java, Media Literacy, Twitter